CSR and value creation: a study among financial institutions in Malaysia / Salina Mad - Mad, Salina (2013)
Financial institutions globally have received considerable amount of pressure from stakeholders to act responsibly and ethically and to be more involved in corporate social responsibility (CSR) practices. However, the ability for financial institutions to fulfill such demands from stakeholders is dependent upon the availability of resources to meet these social causes. It is expected that the involvement of financial institutions in CSR practices can enhance the organizations’ value. As such, this study seeks to examine the relationship between stakeholders’ pressure and internal resources on CSR reporting from the perspective of stakeholder and resource-based theories and the effect o f such disclosure on value creation. The sample for the study was selected from 20 financial institutions in Malaysia over a four-year period from 2008 - 2011 resulting in 76 firms-year observations. Content analyses o f annual and sustainability reports were undertaken to measure the quantity and quality o f CSR disclosure. Value creation was measured using a value-creation index that incorporates both financial and non-financial measures. The results of the study indicate that there is an improvement in the quantity and quality o f CSR disclosure over the four-year period with community dimension being the focus of the CSR activities. Customers were found to be the more influential stakeholders driving the CSR disclosures while concentrated ownership structure inhibits CSR reporting among financial institutions. The quality o f CSR reporting was found to be the determining factor that contributed to firms’ value.